A framework for prospective primary teachers' knowledge of mathematical reasoning processes. (2021) - Rodrigues, Margarida; Brunheira, Lina; Serrazina, Lurdes
Highlights: There are six levels of knowledge within each of the reasoning processes. The three upper levels have an inclusive relation due to their comprehensive nature. Prospective teachers need to develop specialised knowledge of reasoning processes. Abstract: The development of mathematical reasoning is part of the school curricula from the first years, as reflected in teacher education. This study focuses on the prospective primary teachers education, aiming to construct a framework which describes the knowledge about mathematical reasoning processes of teachers and prospective teachers, in the context of a prospective teacher education experiment. Audio and video records of lessons, participant observation and the collection of written records of the prospective teachers are used. The results enable the construction of a framework organised into six levels of knowledge within each of the reasoning processes looked at – generalising, justifying, comparing, classifying and exemplifying – in order to analyse the evolution of this type of knowledge.